Russia Country Report - Avtonomov, Alexei (2000)
Russian Federation consists of 89 Federated units, namely republics, provinces (in Russian - krai), regions (in Russian - oblast), two federal cities (Moscow and Saint-Petersburg), autonomous region and autonomous districts. Federated units are divided in municipalities. Along with the Federal Constitution there are fundamental laws in Federated units (republics have constitutions, all other units have charters). Municipalities (the level of local government) have charters. Each level has its own system of government. And at each level a referendum might be held. Local government approved their regulations on local referenda. Regional laws on referendum and local government regulations on referendum should be consistent with these requirements of the federal law, and local regulation should not contradict both Federal and regional legislation. Therefore, if regional laws were adopted before the mentioned Federal Law entering into force, their parts contradicting with the Federal Law should be amended. In any case, only those provisions of regional laws and local regulations can be used and enforced that conforms to the Federal legislation.